Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036. Issue 22 (18th November 2021) - Chen, Ming-Hong; Lian, Yun-Yang; Fang, Dong-Sheng; Chen, Li; Jia, Jia; Zhang, Wen-Long; Lin, Ru; Xie, Yang; Bi, Hong-Kai; Jiang, Hong
Abstract: The actinomycete strain FIM06-0036 was isolated from marine sponge sample collected from the East China Sea and identified as Verrucosispora sp. based upon the results of 16S rRNA sequence analysis. One new alkaloid, 2-ethylhexyl 1H-imidazole-4-carboxylate (1 ), together with a known alkaloid butyl 1H-imidazole-4-carboxylate (2 ) was obtained from the fermentation products of this strain, the structures of compounds 1 and 2 were determined by their detailed analysis of 1 D, 2 D NMR and HR-ESI-MS data, along with literature data analysis. Compounds 1 and 2 were evaluated for their antimicrobial activity with MIC (minimum inhibitory concentration) values ranging from 8 to 256 μg · mL −1 against Helicobacter pylori, Klebsiella Pneumonia, Staphylococcus aureus and Enterococcus faecalis. Graphical Abstract: